Spinoffs and M&A as drivers of spatial clustering: The evolution of the Dutch banking sector in the Amsterdam region in the period 1850-1993 - Ron Boschma; Rik Wenting (European Regional Science Association (ERSA), 2010)
There is little understanding of how clusters evolve, and where. While dynamic analyses of clusters hardly exist, this is especially true for spatial clustering of service industries. We take an evolutionary perspective to describe and explain why the Dutch banking cluster clustered in the Amsterdam region. This analysis is based on an unique database of all banks in the Netherlands that existed in the period 1850-1993, which were collected by the authors. We examine the extent to which spinoff dynamics, merger and acquisition activity and the location of Amsterdam had a significant effect on the survival rate of Dutch banks during the last 150 years. Doing so, we make a first step in providing an evolutionary explanation for why Amsterdam is the leading banking cluster of the Netherlands. Our analyses demonstrate, among other things, that Amsterdam banks were disproportionally active in acquiring other banks, leading to a further concentration of the banking sector in the Amsterdam region.
Keywords: O18; R00; R11; 330; cluster; cluster life cycle; spinoffs; mergers and acquisitions; banking sector